La protesi d’anca: anything new? - Aprato, A.; Greco, V.; Massè, A. (Lo Scalpello - Journal, 2019)
TOTAL HIP ARTHROPLASTY: ANYTHING NEW? Total hip arthroplasty has been described as “the operation of the 20th century”, thanks to the great outcomes, patient satisfaction and improvement in their quality of life. In the last years, changes have been introduced in terms of surgical indications, approaches, tissue preservation, development of different implants, preoperative management and postoperative protocols. The paper analyses different surgical approaches, in particular the anterior vs the postero-lateral approaches; it focuses on surgical indications, either in younger or in older patients, as well as on implants designs. Uncemented stems are frequently used in total hip arthroplasty; among these, short stems have gained space in the market in selected patients. They allow for preservation of the femoral neck, producing a more physiological load pattern in the proximal femur and reducing stress shielding. In short-term follow-up, most of the short stems provided survival rates similar to standard stems; however, long-term studies are not yet available. The aim of this review is to summarise the advances in hip arthroplasty, the current literature on surgical approaches, stems design, biomechanical aspects and clinical outcomes associated mostly with the length of the femoral component in primary hip replacement.